Prevention through Activity in Kindergarten Trial (PAKT): A cluster randomised controlled trial to assess the effects of an activity intervention in preschool children - Lenz Dorothea; Kriemler Susi; Graf Christine; Ruf Katharina C; Obinger Matthias; Mauer Sonja; Roth Kristina; Lehmacher Walter; Hebestreit Helge (BMC, 2010)
Abstract Background Physical activity and motor skills acquisition are of high importance for health-related prevention and a normal development in childhood. However, few intervention studies exist in preschool children focussing on an increase in physical activity and motor skills. Proof of positive effects is available but not consistent. Methods/Design The design, curriculum, and evaluation strategy of a cluster randomised intervention study in preschool children are described in this manuscript. In the Prevention through Activity in Kindergarten Trial (PAKT), 41 of 131 kindergartens of Wuerzburg and Kitzingen, Germany, were randomised into an intervention and a control group by a random number table stratified for the location of the kindergarten in an urban (more than 20.000 inhabitants) or rural area. The aims of the intervention were to increase physical activity and motor skills in the participating children, and to reduce health risk factors as well as media use. The intervention was designed to involve children, parents and teachers, and lasted one academic year. It contained daily 30-min sessions of physical education in kindergarten based on a holistic pedagogic approach termed the "early psychomotor education". The sessions were instructed by kindergarten teachers under regular supervision by the research team. Parents were actively involved by physical activity homework cards. The kindergarten teachers were trained in workshops and during the supervision. Assessments were performed at baseline, 3-5 months into the intervention, at the end of the intervention and 2-4 months after the intervention. The primary outcomes of the study are increases in physical activity (accelerometry) and in motor skills performance (composite score of obstacle course, standing long jump, balancing on one foot, jumping sidewise to and fro) between baseline and the two assessments during the intervention. Secondary outcomes include decreases in body adiposity (BMI, skin folds), media use (questionnaire), blood pressure, number of accidents and infections (questionnaire), increases in specific motor skills (throwing, balancing, complex motor performance, jumping) and in flexibility. Discussion If this trial proofs the effectiveness of the multilevel kindergarten based physical activity intervention on preschooler's activity levels and motor skills, the programme will be distributed nationwide in Germany. Trial Registration ClinicalTrials.gov Identifier: NCT00623844